ANTI-STRESS ACTIVITY OF SOME PLANTS EXTRACTS OF THE NORTH CAUCASUS FLORA - Dmitry Igorevich Pozdnyakov; Similla Adzhiahmetova; Nadezhda Chervonnaya; Andrey Mamleev; Eduard Oganesyan (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2020)
To date, stress is a common medical and socially significant disease that requires rational pharmacotherapeutic correction.The anti-stress properties of ethnolic and aqueous extracts obtained from leaves of Ribes nigrum L., inflorescences of Gaillardia pulchella Foug., stems of Lysimachia punctata L were studied in this work. Acute stress was modeled by immobilization of rats for 2 hours. The test-extracts were administered per os prophylactically in a dose of 1/20 of LD50 (2000 mg/kg). The following parameters were evaluated: organs mass coefficient (adrenal glands, thymus, spleen), the number of stomach erosion; the biochemical changes in the blood serum (adrenaline, cortisol, total protein and glucose concentration); the mitochondrial function parameters in brain and myocardium (evaluation of mitochondrial pore transitional permeability opening and mitochondrial membrane potential). 70% ethanol extract from Gaillardia pulchella Foug. inflorescences has the highest anti-stress activity, the course application of which contributed to the normalization of the weight index of organs, a decrease in glucose concentration by 64.5% (p <0.05), and cortisol by 73.7% (p <0.05) and adrenaline - 78.9% (p <0.05) in the blood, an increase in total protein level by 62.5% (p <0.05) and stabilization of mitochondrial function. The study showed a high anti-stress activity of 70 % ethanol extract from Gaillardia pulchella Foug. inflorescences.